On the role of the proventricle region in reproduction and regeneration in Typosyllis antoni (Annelida: Syllidae). Issue 1 (December 2016) - Weidhase, Michael; Beckers, Patrick; Bleidorn, Christoph; Aguado, M.
Abstract Background Syllids are a species rich annelid family possessing remarkable regenerative ability, which is not only the response after traumatic injury, but also a key step during the life cycle of several syllid taxa. In these animals the posterior part of the body becomes an epitoke and is later detached as a distinct unit named stolon. Such a sexual reproductive mode is named schizogamy or stolonization. The prostomium and the proventricle, a modified foregut structure, have been proposed to have a control function during this process, though the concrete mechanisms behind it have never been elucidated. Results By using different experimental set-ups, histology and immunohistochemistry combined with subsequent cLSM analyzes, we investigate and document the regeneration and stolonization in specimens ofTyposyllis antoni that were amputated at different levels throughout the antero-posterior body axis. The removal of the anterior end including the proventricle implies an incomplete anterior regeneration as well as severe deviations from the usual reproductive pattern, i.e. accelerated stolonization, masculinization and the occurrence of aberrant stolons. The detailed anatomy of aberrant stolons is described. A histological study of the proventricle revealed no signs of glandular or secretory structures. The ventricle and the caeca are composed of glandular tissue but they are not involved in the reproductive and regenerative processes. Conclusions As in other investigated syllids, the proventricle region has a significant role during stolonization and reproduction processes inTyposyllis antoni . When the proventricle region is absent, anterior and posterior regeneration are considerably deviated from the general patterns. However, proventricle ultrastructure does not show any glandular component, thereby questioning a direct involvement of this organ itself in the control of reproduction and regeneration. Our findings offer a comprehensive starting point for further studies of regeneration and reproductive control in syllids as well as annelids in general.